2017
DOI: 10.6018/eglobal.16.3.256091
|View full text |Cite
|
Sign up to set email alerts
|

Eventos adversos relacionados às práticas assistenciais: uma revisão integrativa

Abstract: Nº 47 Julio 2017Página 605 REVISIONES Eventos adversos relacionados con las prácticas asistenciales: una revisión integradoraEventos adversos relacionados às práticas assistenciais: uma revisão integrativa Adverse events related to assistance practices: an integrative review Objetivo: Identificar las publicaciones científicas sobre eventos adversos relacionados con las prácticas asistenciales y discutir la cultura de seguridad del paciente. Métodos: Se realizó una revisión bibliográfica del tipo integrador, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
(44 reference statements)
1
5
0
12
Order By: Relevance
“…22 Most of the ME notifications were done by Nursing professionals, who are directly involved in the process of medication administration. 23 As regards the severity of the medication errors, it was found that 82% of the errors reached the patients without causing them any harm and that only 5% of the patients required monitoring, results which are close to those obtained in a study conducted in 2014 with values nearing 70% of MEs that reached the patients; 24 in another case, the results show that 42% of the errors reached the patients but without causing them any harm. 25 We highlight that one of the limitations of this study refers to the sample size, since 50 reports of adverse events associated with medication errors were found, which contribute scarce information about both the origin and analysis of the events.…”
Section: /13supporting
confidence: 72%
“…22 Most of the ME notifications were done by Nursing professionals, who are directly involved in the process of medication administration. 23 As regards the severity of the medication errors, it was found that 82% of the errors reached the patients without causing them any harm and that only 5% of the patients required monitoring, results which are close to those obtained in a study conducted in 2014 with values nearing 70% of MEs that reached the patients; 24 in another case, the results show that 42% of the errors reached the patients but without causing them any harm. 25 We highlight that one of the limitations of this study refers to the sample size, since 50 reports of adverse events associated with medication errors were found, which contribute scarce information about both the origin and analysis of the events.…”
Section: /13supporting
confidence: 72%
“…1 Through epidemiological studies, the high incidence of human error-caused adverse events that is frequently demonstrated indicated the need to reconsider and modify the care models, linking them up with the countless global campaigns, programs and projects that guide health team actions. 2 The way healthcare errors are interpreted and acted upon maintains the understanding of punitive or hidden postures. Changing this scenario rests on the health managers' understanding of the error as necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the potentials and weaknesses of the health teams towards adverse events is essential, facilitating the adoption of preventive measures and trust among the professionals. 2 Adverse event reporting is part of health care management and, therefore, part of the responsibilities to manage and help the nurses. Setting up a reporting system allows the professionals to share responsibilities and develop actions that are integrated with the logic of continuing and continuing in-service education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La seguridad del paciente ha sido un tema de estudio en los sistemas de salud, que ha surgido como respuesta a los múltiples eventos adversos que sufren las personas en los centros hospitalarios, situación que se expuso en el año 2000 con la publicación del libro "To Err is Human" (1,2) , el cual cita que los errores médicos producen entre 44.000 y 98.000 muertes al año en Estados Unidos, cifra que supera las muertes ocasionadas por accidentes automovilísticos. Esta situación llevó a la Organización Mundial de la Salud (OMS) a crear un grupo de trabajo para evaluar la seguridad del paciente en los servicios de salud (3) .…”
Section: Introductionunclassified